Synthesis, Characterization and Bioactivity Study of Mixed-ligand Complexes with Some Metal ions for new dithiocarbamate, 8-Hydroxyl quinolone - Lekaa M. Hadi (Journal of Global Pharma Technology, 2016)
A series of  [M(Q)(L)] (where M=Co(II),Ni(II) ,Cu(II), Zn(ll),Cd(ll) and Pd(II) , Q=8-hydroxylquinoline and L= dithiocarbamate ligand) complexes have been  prepared. The new dithiocarbamate compound was characterized using elemental analyses, FT-IR, UV-VIS spectroscopy magnetic moments, 1H and 13C NMR for ligands, thermal gravimetric analysis (TGA), differential thermal gravimetric (DTG). The antibacterial activities of synthesized compound were studied against Esherichia Coli, Staphylococcus aureus, Proteus mirabilis and Pseudomons aerugino, for antifungal activity against Candida albicans and Candida tropicalisKeywords: Mixed ligand complexes, Dithiocarbamate, Spectral dat.